Capacity characterization of uplink NOMA in multi-UAV networks - Tan, Ernest Zheng Hui (2020)
In this paper, non-orthogonal multiple access (NOMA) is investigated as a potential solution to address spectrum scarcity in unmanned aerial vehicle (UAV) communications. In particular, the ergodic capacity of uplink (UL) NOMA is characterized within a stochastic geometry framework for a multi-UAV network comprising a ground station (GS) and multiple UAVs. Our analysis reveals that UL NOMA enables fairness, in terms of ergodic capacity, to be achieved in the multi-UAV network. When compared against conventional UL orthogonal multiple access (OMA), we show that the ergodic capacity and ergodic sum capacity is higher for the proposed UL NOMA transmissions. Thus, the proposed scheme enables higher throughput to be achieved in multi-UAV networks while simultaneously improving spectrum efficiency.